ORIGINAL PAPERThe analysis of anamnesis and the hemodynamic response in tilting patients with recurrent syncope - Lelonek, Małgorzata; Goch, Jan Henryk (Archives of Medical Science, 2005)
Introduction: Vasovagal syncope (VVS) constitutes 70% of all unexplained syncope. In this group of patients (pts.) the head-up tilt test (HUTT) is a basic diagnostic method. The aim of the study was the analysis of anamnesis and of noninvasive hemodynamical parameters (heart rate and blood pressure) in tilting patients with recurrent syncope. Material and methods: 170 patients (pts.) with history of recurrent syncope enrolled in the research. The control group comprised 19 healthy volunteers. In all the anamnesis with the specific data of syncope and HUTT in the Westminster protocol prolonged by nitroglycerin provocation were performed. All pts. were divided into the following groups according to the HUTT outcome: positive HUTT (I group) N=129; mean age 50.6±17.8 yrs, 0.37 males; and negative HUTT (II group) N=41; mean age 50.0±18.3 years, 0.56 males. In the multivariate approach the logistic regression analysis was used to identify from anamnesis and noninvasive hemodynamic parameters the most predictive factor of the positive HUTT. Results: The HUTT explained vasovagal origin of syncope in 129 pts. (76%) of the study group. Group I noted a significant increase (p<0.05) in: the number of syncopes, the prodromal symptoms and typical vasovagal anamnesis (p<0.00000) in comparison to group II. The noninvasive analysis of blood pressure (RR) during the HUTT showed significant differences between the analyzed groups, especially in vasodepressor pts. A significantly lower heart rate was noted in pts. with the cardiodepressive reaction than in pts. with the vasodepressive reaction during the HUTT. In the multifactors analysis the highest sensitivity to positive outcome of the HUTT had the presence of typical vasovagal anamnesis (OR 5.85; 95%CI; 2.72-12.56, p<0.00001). Conclusions: The only parameter, permitting to foresee the positive result of the HUTT was typical of vasovagal syncope anamnesis. Noninvasive estimation of hemodynamical parameters showed disturbances in response to the tilting and did not permit to univocally prognosticate the HUTT outcome.